Hydrophobic porous polysulfone membrane contactors with gravity-driven Ca(OH) absorption for low-energy CO removal from biogas - Durmus, Barbaros; Kocer, Nilufer Nacar; Ozturk, Bahtiyar (Nature Portfolio, 2026)
The upgrading of biogas to biomethane requires efficient and energy-conservative removal of carbon dioxide (CO2) to enhance calorific value and downstream usability. In this study, a gravity-driven hydrophobic polysulfone (PSf) hollow-fiber membrane contactor was systematically evaluated for CO2 removal from a synthetic CH4/CO2 (60/40 v/v) gas mixture under ambient conditions (23 +/- 1 degrees C and 1 atm). Unlike conventional membrane contactor systems that rely on mechanically driven liquid circulation, the present configuration operates without liquid pumping, thereby eliminating liquid-phase energy demand and simplifying system architecture. Comparative experiments were conducted using tap water as a physical absorbent and a low-concentration Ca(OH)(2) solution (0.1 wt%) as a reactive absorbent to assess hydrodynamic, mass transfer, and energy performance under realistic decentralized operating conditions. CO2 removal efficiencies exceeding 90% were achieved for both absorbents at optimized operating conditions (gas flow rate: 122.5 mL min-1; liquid flow rate: 800 mL min-1), with maximum values of 92-93% for tap water and approximately 94% for Ca(OH)(2). The gravity-driven falling-film liquid flow regime promoted effective gas-liquid interfacial contact while minimizing liquid-side mass transfer resistance. Specific energy consumption was calculated by accounting exclusively for gas handling and analytical power requirements, yielding low values of 0.47 kWh kg-1 CO2 for tap water and 0.45 kWh kg-1 CO2 for Ca(OH)(2). Long-term stability tests conducted over 30 days (8 h day-1) demonstrated sustained CO2 removal performance with only gradual efficiency decline, attributed primarily to progressive CaCO3 precipitation rather than membrane wetting or structural degradation. The novelty of this work lies not in the introduction of new membrane materials or absorbents, but in the system-level demonstration of a pump-free, gravity-driven membrane contactor that integrates low energy consumption, operational simplicity, and stable performance. The results provide practical insights into the design of modular, low-maintenance membrane contactor systems for decentralized and energy-efficient biogas upgrading applications.
Keywords: Gravity-Driven Membrane Contactor; Biogas Upgrading; Polysulfone Hollow-Fiber Membrane; Specific Energy Consumption; Long-Term Operational Stability; Decentralized Gas Separation